Functional respiratory disorders : When respiratory symptoms do not respond to pulmonary treatment - Anbar, Ran D. (Respiratory Medicine, 2012)
Many patients with pulmonary complaints fail to improve despite physicians' best efforts. Sometimes, we ascribe this failure to lack of adherence with therapy, or to the severity of the condition. What we often fail to appreciate, however, is that sometimes the lack of improvement can be explained by the patients' psychological states.  The first section of Functional Respiratory Disorders: When Respiratory Symptoms Do Not Respond to Pulmonary Treatment will help clinicians recognize functional respiratory symptoms that can arise as a result of both organic and psychological causes.  The second section of this book provides detailed discussions of such disorders, links to video examples of laryngoscopic evaluation of patients with vocal cord issues, case studies and quizzes.  Examples and exercises that should strengthen the clinician's confidence in identifying and treating these functional conditions are also provided.  Finally, the third section of the book will help the clinician differentiate the patients for whom referral to a mental health provider is mandatory from those for whom other approaches may be useful. For the latter group, the book teaches clinicians to empower themselves by learning how to incorporate various therapies for functional disorders into their practice, including biofeedback, breathing techniques, basic cognitive behavioral therapy techniques, and hypnosis. Links are provided to instructive video examples of biofeedback, hypnosis, and speech therapy.  Practical strategies for obtaining training in these modalities are provided in the appendix.  Functional Respiratory Disorders: When Respiratory Symptoms Do Not Respond to Pulmonary Treatment is an important new book that will help clinicians consider the possible impact of functional contributions to the clinical presentation of every patient with respiratory symptoms and identified respiratory disease.